2019
DOI: 10.1007/jhep07(2019)135
|View full text |Cite
|
Sign up to set email alerts
|

Interpretable deep learning for two-prong jet classification with jet spectra

Abstract: Classification of jets with deep learning has gained significant attention in recent times. However, the performance of deep neural networks is often achieved at the cost of interpretability.Here we propose an interpretable network trained on the jet spectrum S 2 (R) which is a two-point correlation function of the jet constituents. The spectrum can be derived from a functional Taylor series of an arbitrary jet classifier function of energy flows. An interpretable network can be obtained by truncating the seri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 79 publications
0
46
0
Order By: Relevance
“…Graph networks are flexible enough for analyzing multiple objects appears at the LHC, and have been studied in various contexts [16,20,25,41,[117][118][119][120][121][122][123][124]. The graph network in this paper has access to only IRC safe two-point energy correlations [19,21,[96][97][98][125][126][127][128]. It was shown that the network has comparable performance to the CNN in the Higgs jet vs. QCD jet classification [21].…”
Section: Jhep07(2020)111mentioning
confidence: 99%
See 2 more Smart Citations
“…Graph networks are flexible enough for analyzing multiple objects appears at the LHC, and have been studied in various contexts [16,20,25,41,[117][118][119][120][121][122][123][124]. The graph network in this paper has access to only IRC safe two-point energy correlations [19,21,[96][97][98][125][126][127][128]. It was shown that the network has comparable performance to the CNN in the Higgs jet vs. QCD jet classification [21].…”
Section: Jhep07(2020)111mentioning
confidence: 99%
“…The graph network in this paper has access to only IRC safe two-point energy correlations [19,21,[96][97][98][125][126][127][128]. It was shown that the network has comparable performance to the CNN in the Higgs jet vs. QCD jet classification [21]. We use this network for top jet vs. QCD jet classification, and it is a good starting point toward the network whose top tagging performance is comparable to the CNN.…”
Section: Jhep07(2020)111mentioning
confidence: 99%
See 1 more Smart Citation
“…The stress-energy flow [21][22][23] is a particularly powerful probe of jets, since it in principle contains all the information about a jet that is infrared and collinear (IRC) safe [24][25][26]. A variety of observables have been built around the energy flow concept [27][28][29][30][31], including recent work on machine learning for jet substructure [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Then one can apply sophisticated algorithms developed for image recognition. This and related neural network approaches were used for boosted W boson tagging [49,[51][52][53], quark-gluon discrimination [54][55][56], top tagging [50,[57][58][59], generic anti-QCD tagging [60,61], photon identification [62], heavy-flavor tagging [63] and search for BSM particles [64][65][66][67][68][69]. Modern deep learning algorithms trained on HCAL energy deposition images can be used for LLP studies.…”
Section: Introductionmentioning
confidence: 99%